CARK3-mediated ADF4 regulates hypocotyl elongation and soil drought stress in Arabidopsis - Peng, Lu; He, Juan; Yao, Huan; Yu, Qin; Zhang, Qian; Li, Kexuan; Huang, Yaling; Chen, Li; Li, Xufeng; Yang, Yi; Li, Xiaoyi (Frontiers in Plant Science, 2022)
Actin depolymerization factors (ADFs), as actin-binding proteins, act a crucial role in plant development and growth, as well as in response to abiotic and biotic stresses. Here, we found that CARK3 plays a role in regulating hypocotyl development and links a cross-talk between actin filament and drought stress through interaction with ADF4. By using bimolecular fluorescence complementation (BiFC) and GST pull-down, we confirmed that CARK3 interacts with ADF4 in vivo and in vitro. Next, we generated and characterized double mutant adf4cark3-4 and OE-ADF4:cark3-4. The hypocotyl elongation assay indicated that the cark3-4 mutant seedlings were slightly longer hypocotyls when compared with the wild type plants (WT), while CARK3 overexpressing seedlings had no difference with WT. In addition, overexpression of ADF4 significantly inhibited long hypocotyls of cark3-4 mutants. Surprisingly, we found that overexpression of ADF4 markedly enhance drought resistance in soil when compared with WT. On the other hand, drought tolerance analysis showed that overexpression of CARK3 could rescue adf4 drought susceptibility. Taken together, our results suggest that CARK3 acts as a regulator in hypocotyl elongation and drought tolerance likely via regulating ADF4 phosphorylation.